Níveis de Energia Digestível para Leitoas dos 30 aos 60 kg Mantidas em Ambiente Frio (15°C) - Ferreira, Rony Antonio; De Oliveira, Rita Flávia Miranda; Donzele, Juarez Lopes; Tadeu Fialho, Elias; Hannas, Melissa Izabel [UNESP]; De Oliveira Neto, Adhemar Rodrigues; Ferreira, Aloízio Soares (My University, 1999)
Twenty-five gilts, from 30 to 60 kg LW, maintained in cold environment, were used to evaluate the effect of levels of digestible energy (DE) from 3100 to 3700 kcal/kg of diet on the performance, carcass composition and blood serum concentrations of free T3. The daily weight gain was not influenced by the dietary DE level, however, linearly influenced the dietary and protein intakes. The feed:gain ratio linearly improved with the increased of the dietary ED level. The DE intake linearly increased with the inclusion of the soybean oil in the diet. Effect of dietary DE level on the fat and protein deposition rate, that linearly increased and decreased, respectively, was observed. The blood serum concentrations of free T3 linearly increased with the dietary DE level. Dietary DE level did not influence the relative and absolute weights of evaluated organs.
Levels of Digestible Energy for Gilts from 30 to 60 kg in a Cold Environment (15°C)
Keywords: Cold environment; Digestible energy; Growing gilt